New understanding of nano-scale interstitial dislocation loops in BCC iron. (12th October 2017) - Gao, N; Chen, J; Kurtz, R J; Wang, Z G; Zhang, R F; Gao, F
Abstract: Complex states of nanoscale interstitial dislocation loop can be described by its habit plane and Burgers vector. Using atomistic simulations, we provide direct evidences on the change of the habit plane of a 1/2⟨1 1 1⟩ loop from 1 1 1 to 1 1 0 and 2 1 1, in agreement with TEM observations. A new 1 0 0 habit plane of this loop is also predicted by simulations. The non-conservation of the Burgers vector is approved theoretically for: (1) dislocation reactions between loops with different Burgers vectors and (2) the transition between ⟨1 0 0⟩ loops and 1/2⟨1 1 1⟩ loops. The rotation from a 1/2⟨1 1 1⟩ to a ⟨1 0 0⟩ loop has also been explored, which occurs at 570 K for time on the order of 10 s. The dislocation-precipitate phase duality and change of habit plane are then proposed as new features for nano-scale dislocation loops.